Dilema Hukum Dan Keadilan: Kajian Yuridis Atas Rencana Penghapusan Tanah Adat Di Indonesia Tahun 2026 - Taufikur Rohman (CV Rewang Rencang, 2025)
The implementation plan of Article 96 paragraph (1) of PP Number 18 of 2021 in 2026, which requires registration of customary land within a period of five years, raises great concerns because it can cause the loss of customary land status. Through a normative legal approach, this study found that the elimination of customary land has the potential to cause the loss of cultural identity, economic resources, and social inequality. Legal protection based on the principle of substantive justice is the key to maintaining the sustainability of indigenous peoples' rights by balancing the needs of national development with the protection of indigenous peoples' rights in order to realize social justice according to the mandate of the constitution. Keywords: Customary Land, Legal Protection, Land Elimination